2005
DOI: 10.1152/jn.00285.2005
|View full text |Cite
|
Sign up to set email alerts
|

Coding of Tactile Response Properties in the Rat Deep Cerebellar Nuclei

Abstract: Rowland, Nathan C. and Dieter Jaeger. Coding of tactile response properties in the rat deep cerebellar nuclei. J Neurophysiol 94: 1236 -1251, 2005; doi:10.1152/jn.00285.2005. In the lateral hemispheres of the cerebellar cortex, somatosensory responses are represented in a finely grained fractured somatotopy. It is unclear, however, how these responses contribute to the ultimate output of the cerebellum from the deep cerebellar nuclei (DCN). Robust responses of DCN neurons to somatosensory stimuli have been des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
84
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(92 citation statements)
references
References 75 publications
8
84
0
Order By: Relevance
“…To analyze the exact time point at which the chance of spiking is increased, we adapted a convolution method that reforms spiking patterns into a normalized chance of spiking (modified from ref. 31) by replacing each spike in the raster plots with a 1-ms SD Gaussian distribution and summing the results over trials (for detailed explanation see SI Materials and Methods and Fig. S2).…”
Section: Resultsmentioning
confidence: 99%
“…To analyze the exact time point at which the chance of spiking is increased, we adapted a convolution method that reforms spiking patterns into a normalized chance of spiking (modified from ref. 31) by replacing each spike in the raster plots with a 1-ms SD Gaussian distribution and summing the results over trials (for detailed explanation see SI Materials and Methods and Fig. S2).…”
Section: Resultsmentioning
confidence: 99%
“…DCN neurons respond to brief sensory stimuli with an initial excitation, followed by a sequence of inhibition and rebound excitation (Eccles et al, 1974;Rowland and Jaeger, 2005), which likely reflects the feedforward excitation-inhibition input sequence at the Purkinje cells that inhibit DCN neurons. For the rapidly triggered spikes in Purkinje cells evoked during the brief excitatory phase, the direct readout of PF LTD may be crucial for governing synchronization of Purkinje cells along a folium, which receive shared input via the PF system and thus for determining the resulting pause in DCN spiking.…”
Section: Functional Implicationsmentioning
confidence: 99%
“…Until recently, however, whether the strength of this information is reflected in the firing rate of DCN neurons has been less clear. Rowland and Jaeger (2005) showed with recordings from DCN neurons in vivo that as a population, these neurons show increased response amplitudes as the intensity of the stimulus (air puff) is increased. They also showed that the intensity of the stimulus was encoded in the activity of cerebellar granule cells.…”
Section: Purkinje Cells Provide Dcn Neurons With Information Regardinmentioning
confidence: 99%